Molecular cloning and functional analysis of Chinese bayberry MrSPL4 that enhances growth and flowering in transgenic tobacco - Wu, Xiangqi; Zhang, Shuwen; Yu, Zheping; Sun, Li; Liang, Senmiao; Zheng, Xiliang; Qi, Xingjiang; Ren, Haiying (Frontiers in Plant Science, 2023)
Chinese bayberry (Myrica rubra) is an important tree in South China, with its fruit being of nutritional and high economic value. In this study, early ripening (ZJ), medium ripening (BQ) and late ripening (DK) varieties were used as test materials. Young leaves of ZJ, BQ and DK in the floral bud morphological differentiation periods were selected for transcriptome sequencing to excavate earliness related genes. A total of 4,538 differentially expressed genes were detected. Based on clustering analysis and comparisons with genes reportedly related to flowering in Arabidopsis thaliana, 25 homologous genes were identified. Of these, one gene named MrSPL4 was determined, with its expression down-regulated in DK but up-regulated in ZJ and BQ. MrSPL4 contained SBP domain and the target site of miR156, and its total and CDS length were 1,664 bp and 555 bp respectively. The overexpression vector of MrSPL4 (35S::35S::MrSPL4-pCambia2301-KY) was further constructed and successfully transfected into tobacco to obtain MrSPL4-positive plants. Based on the results of qRT-PCR, the relative expression of MrSPL4 was up regulated by 3,862.0-5,938.4 times. Additionally, the height of MrSPL4-positive plants was also significantly higher than that of wild-type (WT), with the bud stage occurring 12 days earlier. Altogether, this study identified an important gene -MrSPL4 in Chinese bayberry, which enhanced growth and flowering, which provided important theoretical basis for early-mature breeding of Chinese bayberry.